Health-related quality of life with sacituzumab govitecan in HR+/HER2− metastatic breast cancer in the phase III TROPiCS-02 trial - Rugo, Hope S.; Schmid, Peter; Tolaney, Sara M; Dalenc, Florence; Marmé, Frederik; Shi, Ling; Verret, Wendy; Shah, Anuj; Gharaibeh, Mahdi; Bardia, Aditya; Cortes, Javier (The oncologist, 2024)
The TROPiCS-02 study (NCT03901339) demonstrated that sacituzumab govitecan (SG) has superior clinical outcomes over treatment of physician’s choice (TPC) chemotherapy in patients with hormone receptor-positive, human epidermal growth factor 2 receptor-negative (HR+/HER2−) metastatic breast cancer (mBC). Here, we present health-related quality of life (HRQoL) patient-reported outcome (PRO) findings from this study.Eligible adults with HR+/HER2− mBC who previously received a taxane, endocrine-based therapy, a CDK4/6 inhibitor, and 2-4 lines of chemotherapy were randomized 1:1 to receive SG or TPC until progression or unacceptable toxicity. PROs were assessed at baseline and on day 1 of each cycle, using the European Organization for Research and Treatment of Cancer Quality-of-Life Core 30 (EORTC QLQ-C30), EQ-5D-5L, and PRO Common Terminology Criteria for Adverse Events (PRO-CTCAE).Compared to TPC, overall least square mean change from baseline was significantly better for SG for physical functioning and dyspnea, but worse for diarrhea. Time to first clinically meaningful worsening or death was significantly longer for SG in global health status/quality of life, physical functioning, fatigue, emotional functioning, dyspnea, insomnia, and financial difficulties of the EORTC QLQ-C30 and the EQ-VAS, but longer for TPC in diarrhea. Few patients in both arms reported experiencing any worsening to level 3 or 4 treatment-related symptomatic events during treatment, as assessed by 16 PRO-CTCAE items, except for diarrhea frequency and amount of hair loss, which favored TPC.SG was associated with an HRQoL benefit in most symptoms and functioning, compared with TPC. This supports the favorable profile of SG as a treatment option for patients with pretreated HR+/HER2− mBC.
Online veröffentlicht: 15. Mai 2024
Gesehen am 09.12.2024